Implementation of Content Marketing and FOMO (Fear of Missing Out) Marketing on Instagram @Espangeran_ to Increase Gen Z Consumer Loyalty - Anastasya S, Aisyah Afifah; Siregar, Zulkarnain (Economic: Journal Economic and Business, 2025)
This study aims to examine how the Instagram account @espangeran_ utilizes content marketing strategies and FOMO (Fear of Missing Out) marketing to build and maintain customer loyalty among Generation Z. In today's highly competitive digital era, the use of social media has become a crucial tool for marketing, especially in reaching young, digitally active consumers. This research combines a descriptive qualitative approach with a quantitative method through questionnaires and analysis of content activities on the @espangeran_ Instagram account. The study reveals that the integration of relevant, innovative, and interactive content with FOMO strategies—such as the use of time urgency, product exclusivity, and user testimonials—significantly contributes to the development of emotional connections with Gen Z customers.